Understanding the body: learning how Puerto Rican women in New York City receive information on reproductive health - Calderon Hooper, Emily Marie, author; Vernon, Irene, advisor; Souza, Caridad, committee member; Aragon, Antonette, committee member (Colorado State University. Libraries, 2015)
This qualitative study explores the experiences and stories of eleven self-identified second and third generation Puerto Rican women raised and living in New York City. Through semi-structured focus groups conducted in New York City, this study deconstructs how the women in this study learn and understand their bodies in the context of reproductive health. Furthermore, it aims to be liberatory in nature and to engage in practices that center the voices and experiences of the women participating. This study comprises decolonial and critical feminist frameworks and epistemologies and argues that second and third generation Puerto Rican women raised in New York City understand their bodies in relation to reproductive health in a multitude of ways. This study shows that reproductive health for Puerto Rican women in New York City should not be framed within a victim/agent dichotomy, because the experiences of these women are more nuanced and complicated. This thesis also reveals that transmission of reproductive healthcare resources from medical professionals to these women is severely limited and lacking. It is recommended that the experiences of Puerto Rican women in reproductive health be valued and incorporated into peer-to-peer workshops and promotora healthcare models to enhance how Puerto Rican women in New York City receive information on reproductive health.